The Social Economy Model Based on Pesantren Communities in the Post-Truth Era - Zulfatun Anisah (PAPUA: International Journal of Sharia Business Management, 2025)
The rise of the post-truth era—marked by the prioritization of emotions over facts and the widespread manipulation of information—has challenged the sustainability and credibility of conventional socio-economic models. In contrast, pesantren communities in Indonesia have preserved a unique social economy rooted in Islamic values, communal trust, and productive religiosity. This study investigates the structural and functional characteristics of the social economy practiced by pesantren communities and how these values serve as a resilient framework amid post-truth dynamics. Using a qualitative case study method, data were collected through in-depth interviews, focus group discussions, and participatory observations in five pesantren-based business units across East Java. The analysis reveals that pesantren communities build their economic activities on the principles of collective welfare (maslahah), transparency (amanah), and intergenerational trust. These elements shape a distinctive ecosystem that integrates religious authority, social capital, and economic inclusiveness. The findings confirm that the pesantren-based social economy not only offers an alternative to mainstream capitalist models but also provides a robust foundation for resisting the socio-economic disintegration caused by post-truth narratives. This model strengthens local resilience, promotes ethical entrepreneurship, and fosters economic justice in marginalized societies.